Clinical Features and Management of Skull Base Fractures in the Pediatric Population: A Systematic Review - Geena Jung; Jorden Xavier; Hailey Reisert; Matthew Goynatsky; Margaret Keymakh; Emery Buckner-Wolfson; Timothy Kim; Ryan Fatemi; Seyed Ahmad Naseri Alavi; Andres Pasuizaca; Pushti Shah; Genesis Liriano; et al. (MDPI AG, 2024)
Pediatric basilar skull fractures (BSFs) are a rare type of traumatic head injury that can cause debilitating complications without prompt treatment. Here, we sought to review the literature and characterize the clinical features, management, and outcomes of pediatric BSFs. We identified 21 relevant studies, excluding reviews, meta-analyses, and non-English articles. The incidence of pediatric BSFs ranged from 0.0001% to 7.3%, with falls from multi-level heights and traffic accidents being the primary causes (9/21). The median presentation age ranged from 3.2 to 12.8 years, and the mean age of patients across all studies was 8.68 years. Up to 55% of pediatric BSFs presented with intracranial hematoma/hemorrhage, along with pneumocephalus and edema. Cranial nerve palsies were a common complication (9/21), with the facial nerve injured most frequently (7/21). While delayed cranial nerve palsy was reported in a few studies (4/21), most resolved within three months post-admission. Other complications included CSF leaks (10/21) and meningitis (4/21). Management included IV fluids, antiemetics, and surgery (8/21) to treat the fracture directly, address a CSF leak, or achieve cranial nerve compression. Despite their rarity, pediatric skull base fractures are associated with clinical complications, including CSF leaks and cranial nerve palsies. Given that some of these complications may be delayed, patient education is critical.